2012
DOI: 10.1111/j.1467-2995.2012.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a minimally invasive non–calibrated pulse contour cardiac output monitor (FloTrac/Vigileo) in anaesthetized dogs

Abstract: Objective  To evaluate the accuracy of a new cardiac output monitor (FloTrac/Vigileo), originally designed for humans, in dogs. This pulse contour cardiac output monitoring system cannot be calibrated and measures cardiac output (Q̇t) from a standard arterial catheter. Study design  Prospective experimental trial. Animals  Eight adult Beagle dogs weighing 13.1 (9.8–17.1) kg [median (range)]. Methods  Anaesthesia in the dogs was maintained using isoflurane. A pulmonary artery catheter and a metatarsal arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…In agreement with the current study, previous findings in dogs have also shown the accuracy and precision of FloTrac V1.10 with TD (Bektas et al. ) and LiDCO (Valverde et al. ) to be insufficient.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with the current study, previous findings in dogs have also shown the accuracy and precision of FloTrac V1.10 with TD (Bektas et al. ) and LiDCO (Valverde et al. ) to be insufficient.…”
Section: Discussionsupporting
confidence: 93%
“…We employed the Vigileo Flo‐Trac sensor to estimate SVV. Although this system has been shown to overestimate CO in isoflurane anesthetized dogs due to a higher degree of dependence on arterial blood pressure, it has been shown to be a sensitive indicator of dynamic circulating blood volume changes …”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, this requirement has been overlooked in many cases, and still many investigators use the classical Bland‐Altman plot for replicate measurements (Bektas et al. ; Garofalo et al. ; Seliskar et al.…”
Section: Bland Altman Plotsmentioning
confidence: 99%